Distribution and diversity of viruses infecting yams (Dioscorea spp.) in Cameroon - Azeteh, I.N.; Hanna, R.; Njukeng, A.P.; Oresanya, A.O.; Sakwe, P.N.; Kumar, P. Lava (Springer, 2019)
Yam (Dioscorea spp.) is an important food crop cultivated for its edible tubers in Cameroon. Surveys were conducted in Cameroon to determine the incidence and severity of yam mosaic disease and associated viruses in 124 yam farms in four agro-ecological zones in 2014 and 2016. Dioscorea rotundata, D. cayenensis, D. alata, D. Dumetorum and D. bulbifera were most frequently detected yam species in the fields. Symptoms of virus disease were observed on 81.5% of the farms surveyed and the disease incidence ranged from 0 to 96.7%, with an overall mean of 26.5%. Mean symptom severity estimated using a numerical rating scale of 1–5, ranged from 2 to 4.1, with an overall mean of 2.6. Representative set of leaf samples collected from farmers’ fields were tested for three viruses known to cause yam mosaic disease in West Africa, viz., Yam mosaic virus (YMV), Yam mild mosaic virus (YMMV) and Cucumber mosaic virus (CMV), using multiplex RT-PCR. YMV and YMMV were detected in 220 (37.2%) of the 591 samples tested and 75% of the farms surveyed. None of the samples tested positive to CMV. Phylogenetic analysis based on the coat protein sequencing of 27 YMV isolates clustered these isolates into three phylogenetic groups. This study demonstrated high prevalence of mosaic disease in yam fields and YMV as main causal agent. Knowledge generated in this study will be useful to augment diagnostic tools and yam mosaic disease control with a view to improve on yam production in Cameroon.